OPTIMIZING QUR'AN MEMORIZATION THROUGH THE APPLICATION OF ILQA’ MUFRADAT - Hidayah, Karomatul; Rido Kurnianto; Aldo Redho Syam (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
This study aims to analyze the optimization of Qur'an memorization through the application of Ilqa’ Mufradat, as some memorizers use vocabulary as cues to facilitate memorization and enhance their understanding of Arabic. The Ilqa’ Mufradat method is a learning approach that integrates the mastery of Arabic vocabulary into the Qur'an memorization process.This research uses a qualitative approach. Data collection techniques include observation, interviews, and documentation. The data sources consist of the Ilqa’ Mufradat instructor, halaqah (Qur’anic study circle) teacher, Arabic language instructor, and the students. The results of the study show that the implementation of Ilqa’ Mufradat involves planning, execution, and evaluation stages. A structured application of Ilqa’ Mufradat has been shown to improve students’ understanding and retention of memorized verses. This is evident from the Arabic vocabulary sessions and evaluations, which indicate that the students’ average scores exceed the minimum competency standard—namely, scores above seven. The students' Qur'an memorization is considered good, as shown by their achievement of the monthly target of one juz per month.